A framework of servant leadership impact on job performance: the mediation role of employee happiness in UAE healthcare sector - Alahbabi, Abdulla Mohammed Fahed Muaid; Robani, Anidah; Al-Shami, Samer Ali Hussein (Allied Business Academies, 2021)
Servant leadership influences the behaviors of human resources by increasing the happiness of employees and fostering their performance. Moreover, this leadership style focuses on the needs of individuals, and serves followers to fulfill these needs. People who accept servant leadership experience higher levels of satisfaction, trust, creativity, recognition and independence in their work. Today, many organizations in the healthcare sector are facing various challenges associated with human resources. One of these challenges is the absence of a strategy to make employees happy at the workplace. Another challenge is finding the appropriate leadership style, which enhance job performance. Hence, the issue of happiness at the workplace needs to be properly conceptualized so that to understand the role of leadership from different perspective. Accordingly, this study developed a conceptual framework that constructs employee happiness as a mediator between servant leadership and job performance. The methodology adopted in this study is quantitative, whereas the survey has been conducted in Abu Dhabi Health Services Company (SEHA). The Population represents the employees and administrative staff. The result reveals that the empirical data has a satisfactory degree of fit with the conceptual framework. The findings of this study contributed to the body of knowledge in servant leadership and happiness at the workplace. Moreover, it shows that the performance of human resources in healthcare institutions can be improved if the organizations adopted servant leadership style.